2004
DOI: 10.1101/gr.2363004
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of a Function Involving Gene Duplication by Retroposition in Saccharomyces cerevisiae

Abstract: The duplication of DNA sequences contributes to genomic plasticity and is known to be one of the key factors responsible for evolution. The mechanisms underlying these rare events, which have been frequently mentioned by authors performing genomic analysis, have not yet been completely elucidated. These mechanisms were approached here in the yeast Saccharomyces cerevisiae, using a positive selection screen based on a particular mutated allele of the URA2 gene. Spontaneous revertants containing a duplication of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
47
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 43 publications
(41 reference statements)
1
47
0
Order By: Relevance
“…Thus, retroposition in Drosophila seems to occur via a microsimilarity-dependent template switch mechanism of LTR retrotransposons, which is analogous to the one reported for retroviruses and yeast (Goodrich and Duesberg 1990;Luo and Taylor 1990;Derr et al 1991;Hajjar and Linial 1993;Schacherer et al 2004). One implication of this mechanism is that both 5…”
Section: Gypsy 12mentioning
confidence: 76%
See 1 more Smart Citation
“…Thus, retroposition in Drosophila seems to occur via a microsimilarity-dependent template switch mechanism of LTR retrotransposons, which is analogous to the one reported for retroviruses and yeast (Goodrich and Duesberg 1990;Luo and Taylor 1990;Derr et al 1991;Hajjar and Linial 1993;Schacherer et al 2004). One implication of this mechanism is that both 5…”
Section: Gypsy 12mentioning
confidence: 76%
“…The evidence for this process is, however, very limited. In yeast, reporter assays demonstrated that the LTR retrotransposon Ty can capture partial mRNA sequences and form a chimera consisting of internal retrocopies flanked by the retrotransposon, and this is often accompanied by microsimilarity at the fusion points (Derr et al 1991;Schacherer et al 2004). In maize, a chimera consisting of partial sequences derived from three unlinked cellular genes flanked by the LTR retrotransposon Bs1 has been described Bureau 2001, 2010); in rice, 27 retrocopies were found to be located within LTR retrotransposons (Wang et al 2006).…”
mentioning
confidence: 99%
“…In the yeast Saccharomyces cerevisiae, Ty retrotransposons have been shown to play a significant role in mediating genomic rearrangements, including gene amplifications (see Mieczkowski et al 2006 for a review). These changes have been shown to occur under many different growth conditions, including selections for increased gene expression or drug resistance, after stress, or spontaneously (for examples, see Liebman et al 1981;Brown et al 1998;Rachidi et al 1999;Hughes et al 2000;Dunham et al 2002;Koszul et al 2004;Schacherer et al 2004;Selmecki et al 2006;Argueso et al 2008). A recent study showed that Tymediated amplifications are a common occurrence when S. cerevisiae is grown under conditions limiting for glucose, phosphate, or sulfate (Gresham et al 2008).…”
mentioning
confidence: 99%
“…Experimental systems to detect retrosequence formation are limited by extremely low frequencies of events (Schacherer et al 2004), or they rely on overexpression of the donor genes and/or retroelements (Derr et al 1991;Esnault et al 2000). We reported that retrosequences of subtelomeric YЈ elements form frequently in Saccharomyces cerevisiae strains that lack telomerase (Maxwell et al 2004).…”
mentioning
confidence: 99%